Optimization of Real-Time PCR-melting for detection of the Cholesterol-deficiency mutation in Holstein Friesian cattle - Branda-Sica, Andrea; Nicolini, Paula; Artigas, Rody; Federici, Maria Teresa; Llambi, Silvia (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The purpose of this study was to optimize a real-time PCR-melting analysis for reliable and economical detection of the 7.5 Kb mutant insert of the BoERVK bovine transposable element in exon 5 of the Apolipoprotein B (APOB) gene, which causes cholesterol deficiency — CD — (OMIA 001965-9913). This technique was also used to perform a preliminary molecular screening to detect this mutation in a DNA sample of Holstein Friesian cows (HFc) of six commercial dairy farms from different regions of Uruguay. By amplifying the 170 and 146 bp PCR products, two genotypes were clearly identified: homozygote (wild type wt/wt) and heterozygote (carrier of the CD mutation: MUT/wt). The homozygous wt/wt genotype was detected in the representative sample of 103 HFc. It is concluded that Real-Time PCR-melting analysis is a fast, easily interpretable, low cost, and highly accurate technique for detecting this mutation, which can be implemented in genetic selection programs to prevent the spread of the disease in HFc